Numerical Study on Aerodynamic Characteristics of Parachute Models for Future Jupiter Exploration - He Jia; Wenlong Bao; Wei Rong; Li Yu; Xiaopeng Xue; Jianhui Fan (Space: Science & Technology, 2024)
At present, the key technical researches are carried out for the future exploration missions to dense atmosphere planets such as Jupiter. As a necessary aerodynamic decelerator for planetary exploration missions with dense atmosphere, parachutes face several big challenges, such as complex transonic/supersonic unsteady aerodynamic characteristics. Thus, it is necessary to study deeply and make clear the transonic/supersonic unsteady flow mechanisms around the parachute systems and its aerodynamic characteristics; however, these are still unknown to date. In this study, parachute structure systems are designed based on the Galileo exploration mission. Using the parachute models, the numerical simulations were conducted to investigate the complex flow phenomena and unsteady aerodynamics of parachute systems with different diameter ratios of capsule to canopy, under different freestream Mach numbers. As a result, it is found that when a parachute 2-body model with a bigger diameter ratio of capsule to canopy is placed in transonic flows, the wake of the forebody (capsule) is strong, and the shock wave in front of the canopy is weak. When the canopy shock moves upstream, the pressure fluctuation inside the canopy surface exhibits 3 stages of changes: high-frequency large-amplitude, low-frequency small-amplitude, and high-frequency small-amplitude. It is also found that in the supersonic flow cases, the amplitude and frequency of pressure fluctuations inside the canopy increase significantly, especially at Mach 2.0. This is due to the strong interactions between the shedding vortex of the wake and the shock wave in front of the canopy. However, for the parachute model with a small diameter ratio, the important shock waves in front of the canopy is not observed, and high-frequency and small-amplitude pressure variations remain, which is affected directly by the frequency and intensity of wake vortex shedding. In summary, as the Mach number increases, the amplitude and frequency of pressure fluctuations increase, and the average pressure distribution also increases, and the law of its influence becomes more complex.